2020
DOI: 10.3389/fphar.2020.00266
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Pain Sensitivity by Chronic Consumption of Highly Palatable Food Followed by Abstinence: Emerging Role of Fatty Acid Amide Hydrolase

Abstract: There is a strong relationship between palatable diet and pain sensitivity, and the cannabinoid and opioid systems might play an important role in this correlation. The palatable diet used in many animal models of obesity is the cafeteria (CAF) diet, based on human food with high sugar, salt, and fat content. In this study, we investigated whether long-term exposure to a CAF diet could modify pain sensitivity and explored the role of the cannabinergic system in this modification. Male Sprague-Dawley rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 110 publications
(125 reference statements)
1
4
0
Order By: Relevance
“…FAAH inhibition also induced a significant reduction of CB1 receptor expression, whose activation has been linked both to anxiolytic and anxiogenic response in a dose‐dependent manner (Rubino et al, 2008). These results are consistent with existing research on the role of PF‐3845 in the modulation of the ECS in the brain (Bedse et al, 2018; Cifani, Avagliano, et al, 2020; Hruba et al, 2015), suggesting that PF‐3845 increases brain acylethanolamides tone. Of course, it is important to emphasize that PF‐3845 was chronically administered in the current study; thus, some of the effects shown in our study might reflect a compensation to chronic FAAH inhibition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…FAAH inhibition also induced a significant reduction of CB1 receptor expression, whose activation has been linked both to anxiolytic and anxiogenic response in a dose‐dependent manner (Rubino et al, 2008). These results are consistent with existing research on the role of PF‐3845 in the modulation of the ECS in the brain (Bedse et al, 2018; Cifani, Avagliano, et al, 2020; Hruba et al, 2015), suggesting that PF‐3845 increases brain acylethanolamides tone. Of course, it is important to emphasize that PF‐3845 was chronically administered in the current study; thus, some of the effects shown in our study might reflect a compensation to chronic FAAH inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…We chose to treat the rats every other day since PF‐3845 is a covalent FAAH inhibitor with a long‐lasting pharmacological action (Ahn, Johnson, Mileni, et al, 2009), allowing the animals to be treated in alternate days and reducing handling stress. PF‐3845 dosage (10 mg/kg) was chosen according to previous studies (Cifani, Avagliano, et al, 2020; Nasirinezhad et al, 2015; Natividad et al, 2017; Rock et al, 2015; Sakin et al, 2015). The experimental design is depicted in Figure 2a.…”
Section: Methodsmentioning
confidence: 99%
“…Animals pre-treated with the FAAH inhibitor URB597 did not show these satiety responses following leptin treatment, suggesting that FAAH inhibition suppresses the effects of leptin on body weight and food intake. In another study, pharmacological inhibition of FAAH with PF-3845 had no effect on energy storage in rats [27]. Following exposure to a high-fat diet, PF-3845 and saline-treated animals showed similar decreases in body weight and food intake.…”
Section: Animal Studies Involving Pharmacological Manipulationmentioning
confidence: 95%
“…Since no significant differences in body weight ( p > 0.05) and food intake ( p > 0.05) were detected, rats were randomly divided into two experimental groups as follows (n = 18 in each group): animal fed with chow only, called CHOW rats and animal fed 24 h with both chow and extended access to CAF diet for 84 days, called CAF rats. The CAF diet, previously described [ 95 , 96 ], consisted of mortadella (3.2 kcal/g), cookies (Macine, Mulino Bianco; 4.8 kcal/g), chocolate muffin (Mr Day, Vicenzi group; 4.5 kcal/g), cheese chips (Fonzies; 5.3 kcal/g), cheese (Biraghi cheese, 4.2 kcal/g), sippets (San Carlo; 5.5 kcal/g) and lard (9 kcal/g), which were individually weighed before being made available to the rats. Each group was divided into two subgroups (n = 9 in each group): control groups (CHOW or CAF rats) and supplemented groups with L. plantarum IMC 510 probiotic strain (CHOW+P or CAF+P).…”
Section: Methodsmentioning
confidence: 99%